Ensino de habilidades sociais no Transtorno do Espectro Autista na adolescência e vida adulta: uma revisão de estudos em análise do comportamento - Gusmão, Thiago Barbosa (2023)
With the increasing prevalence of Autism Spectrum Disorder, worldwide concern about behavioral interventions in Experimental Behavior Analysis is slowly increasing for adolescents and adults, relative to the pediatric group. The present study carried out a literature review of experimental studies in Behavior Analysis, on Teaching Social Skills to adolescents and adults with ASD. The search was performed on PsycINFO, PubMed and Web of Science platforms. Thirteen experimental studies on the subject were selected, evidencing a lack of investigations for this population. Most study participants are male adolescents and adults, with vocal behavior and IQ > 70, when reported. Ten teaching procedures (VIs) were identified, and researchers often associate several; the most used being Feedback and Oral Instructions. Twenty-eight behaviors taught in social skills studies were identified, with vocal interaction and non-vocal interaction being the most taught. Most studies did not describe important dimensions about maintenance and generalization. It was concluded that Behavior Analysis can effectively contribute to the implementation of social skills teaching programs for this public. The need for new behavioral-analytical studies emerges, aiming at interventions that can be replicated with the adolescent and adult population, thus filling the gaps and limitations still present in our field of study